Impact of Temperature and Solar Radiation on Photovoltaic Cell Efficiency: A Simulation Study Using MATLAB (The International Journal of Engineering & Information Technology (IJEIT), 2025)
This research targets studying the impact of temperature and solar radiation on two types of photovoltaic cells: monocrystalline and polycrystalline. This paper examines, through the use of MATLAB simulation, the variation in these environmental factors for significant parameters such as efficiency, power output, and voltage characteristics in order to deduce the superior performance type under high-temperature conditions. This was simulated for temperature and solar radiation variations from 25°C to 65°C, in 10°C steps, and 200 W/m² to 1000 W/m², in 200 W/m² steps, respectively. For both types of cells, constants, variables, and specifications were programmed into MATLAB, while iterative loops calculated the behavior of the cells under these conditions. Results have been presented as performance curves and graphs that relate temperature and solar radiation with the performance of photovoltaic cells. From the results, it can be obtained that monocrystalline cells are more efficient in the test conditions described because of their being less affected by temperature rises compared to the polycrystalline ones. The investigation clearly shows how the choice of different photovoltaic technologies must take into consideration meteorological factors, especially for zones with high temperatures or variable radiation.